2009
DOI: 10.1681/asn.2008111148
|View full text |Cite
|
Sign up to set email alerts
|

Chromogranin A Regulates Renal Function by Triggering Weibel–Palade Body Exocytosis

Abstract: Chromogranin A (CHGA), a protein released from secretory granules of chromaffin cells and sympathetic nerves, triggers endothelin-1 release from endothelial cells. CHGA polymorphisms associate with an increased risk for ESRD, but whether altered CHGA-endothelium interactions may explain this association is unknown. Here, CHGA led to the release of endothelin-1 and Weibel-Palade body exocytosis in cultured human umbilical vein endothelial cells. In addition, CHGA triggered secretion of endothelin-1 from glomeru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
34
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 40 publications
0
34
0
Order By: Relevance
“…Elevations in circulating levels of other potential mediators of progressive renal damage have been reported; however, it is difficult to ascribe a cause and effect to such associations. In the study by Chen et al, 1 the authors propose that levels of CHGA-stimulated release of endothelin depend on genotype and are accurately mirrored by levels in the circulation; however, as with previous studies, it is difficult to ascribe a causative role in decreased GFR to either the level of circulating CHGA or endothelin. Thus, although individuals with ESRD have higher plasma levels of CHGA than those with CKD and both were higher than in normal individuals, it is unclear whether genetic variation affects plasma levels that mediate the decline in renal function or the impairment in renal function alters CHGA metabolism and/or excretion with consequent increases in plasma level.…”
mentioning
confidence: 94%
See 4 more Smart Citations
“…Elevations in circulating levels of other potential mediators of progressive renal damage have been reported; however, it is difficult to ascribe a cause and effect to such associations. In the study by Chen et al, 1 the authors propose that levels of CHGA-stimulated release of endothelin depend on genotype and are accurately mirrored by levels in the circulation; however, as with previous studies, it is difficult to ascribe a causative role in decreased GFR to either the level of circulating CHGA or endothelin. Thus, although individuals with ESRD have higher plasma levels of CHGA than those with CKD and both were higher than in normal individuals, it is unclear whether genetic variation affects plasma levels that mediate the decline in renal function or the impairment in renal function alters CHGA metabolism and/or excretion with consequent increases in plasma level.…”
mentioning
confidence: 94%
“…One of the challenges presented by these studies is to define the mechanisms by which a given genetic variant affects a pathophysiologic disorder. This inevitable quandary confronts the study of Chen et al 1 in this issue of JASN. The authors previously reported that a genetic polymorphism of chromatogranin A (CHGA), a soluble protein released from secretory granules of chromaffin cells and sympathetic nerves, predicts hypertensive ESRD in black patients.…”
mentioning
confidence: 97%
See 3 more Smart Citations